A Comparative Longitudinal Study Analyzing Vaginal Microbiota Differences Between Term and Preterm Pregnancies in Korean Women - Gina Nam; Kyung A. Lee; Soo Jung Kim; Kwan Young Oh; Sunghee Lee; Hyun Chul Lee; So Yoon Kim; Mi Hye Park (Medicina)
Background and Objectives: Preterm birth (PTB), defined as delivery before 37 weeks of gestation, remains a significant public health concern due to its association with neonatal morbidity and mortality. Although studies have suggested that microbial factors in vaginal microbiota (VMB) influence PTB, longitudinal research on Korean women is limited. This study aimed to analyze VMB differences between term and preterm pregnancies in Korean women and their correlation with the cervical length (CL). Materials and Methods: A cohort of 60 pregnant Korean women (40 who had a term birth (TB) and 20 who had a PTB) was recruited. Vaginal samples were collected at five time points (first, second, and third trimester; 1–2 weeks postpartum; 1–2 months postpartum). Microbial DNA was extracted and analyzed using quantitative PCR targeting 12 bacterial species. The CL was measured in the second and third trimesters. Results: Lactobacillus crispatus was consistently dominant in the TB group, whereas PTB cases exhibited greater microbial diversity with elevated levels of Prevotella salivae and Ureaplasma species. The CL was significantly shorter in PTB cases, correlating with shifts in the VMB composition. Conclusions: A stable, Lactobacillus-dominant microbiome is protective in pregnancy, while increased diversity in PTB cases suggests microbial biomarkers for early risk prediction. Combining VMB profiling with CL measurement may enhance early, non-invasive PTB risk assessments.